2019
DOI: 10.3389/fgene.2019.00055
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Transcriptome Analyses Reveal Short-Term Responses and Formation of Memory Under Drought Stress in Rice

Abstract: In some plants, exposure to stress can induce a memory response, which appears to play an important role in adaptation to recurrent stress environments. However, whether rice exhibits drought stress memory and the molecular mechanisms that might underlie this process have remained unclear. Here, we ensured that rice drought memory was established after cycles of mild drought and re-watering treatment, and studied gene expression by whole-transcriptome strand-specific RNA sequencing (ssRNA-seq). We detected 6,8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
129
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(140 citation statements)
references
References 66 publications
8
129
0
3
Order By: Relevance
“…When exposed to drought again, although the expressions of most of them were slightly lower than the initial drought-induced expression, they were still upregulated by re-drought ( Figure 8). They might be involved in the early response of plants to drought and affected by the drought hardening, which was similar to the ABA signal in Arabidopsis and rice participating in drought memory response after repeated drought treatments [13,22]. It is suggested that ABA signal plays an important role in the response of drought resistance and also in the improvement of subsequent drought resistance in plant.…”
Section: Perception and Transmission Of Drought Stress Signalsmentioning
confidence: 68%
See 4 more Smart Citations
“…When exposed to drought again, although the expressions of most of them were slightly lower than the initial drought-induced expression, they were still upregulated by re-drought ( Figure 8). They might be involved in the early response of plants to drought and affected by the drought hardening, which was similar to the ABA signal in Arabidopsis and rice participating in drought memory response after repeated drought treatments [13,22]. It is suggested that ABA signal plays an important role in the response of drought resistance and also in the improvement of subsequent drought resistance in plant.…”
Section: Perception and Transmission Of Drought Stress Signalsmentioning
confidence: 68%
“…The regulation of plant drought tolerance includes not only the key signaling metabolites and hormones, but also their activity-regulating proteins, such as kinases/phosphatases and TFs [13]. ABA is an important signal molecule in response to drought stress.…”
Section: Perception and Transmission Of Drought Stress Signalsmentioning
confidence: 99%
See 3 more Smart Citations